2018
DOI: 10.1002/ptr.6130
|View full text |Cite
|
Sign up to set email alerts
|

Green tea as a safe alternative approach for nonalcoholic fatty liver treatment: A systematic review and meta‐analysis of clinical trials

Abstract: This study aimed to evaluate the efficacy of green tea supplementation on nonalcoholic fatty liver disease treatment. Electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar, were systematically searched up to October 30, 2017, to identify eligible trials based on the inclusion criteria. The effect size was presented as mean difference with 95% confidence intervals (CI). The meta-analysis of data from four studies indicated significant effects of green tea supplementation in altering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 43 publications
0
32
1
1
Order By: Relevance
“…Our findings were in contrast with previous meta‐analysis (Mansour‐Ghanaei et al, ) regarding ALT, but similar for AST. The mentioned study was relatively small compared with our systematic review and meta‐analysis (included 315 subjects from six RCTs) because only four RCTs (228 subjects) were included in aforesaid meta‐analysis which makes our study more reliable in terms of provided results.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings were in contrast with previous meta‐analysis (Mansour‐Ghanaei et al, ) regarding ALT, but similar for AST. The mentioned study was relatively small compared with our systematic review and meta‐analysis (included 315 subjects from six RCTs) because only four RCTs (228 subjects) were included in aforesaid meta‐analysis which makes our study more reliable in terms of provided results.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to human studies, investigations on animal species revealed that propolis and its ingredient are safe and do not cause any toxic changes in the liver and kidneys (Celik & Erdogan, ; Jung et al, ; Türkez, Yousef, & Geyikoglu, ). Although propolis, like many alternative remedies, is generally better tolerated than synthetic medications (A. Hadi, Pourmasoumi, Najafgholizadeh, Kafeshani, & Sahebkar, ; Izzo, Hoon‐Kim, Radhakrishnan, & Williamson, ; Mansour‐Ghanaei, Hadi, Pourmasoumi, Joukar, Golpour, & Najafgholizadeh, ), several studies have suggested that propolis had the potential for allergic reactions in certain people. It might cause skin to redden or rashes to develop, itch, and swell.…”
Section: Discussionmentioning
confidence: 99%
“…Green tea extract (GTE) is known as a bona fide herbal therapy for NAFLD and obesity (Mansour‐Ghanaei et al, ; Yang & Hong, ). Most of these health effects are due to the polyphenols and alkaloids.…”
Section: Introductionmentioning
confidence: 99%